Insulin sensitivity and kinetics in African American and White people with obesity: Insights from different study protocols. Issue 3 (27th January 2022) - Koh, Han‐Chow E.; Patterson, Bruce W.; Reeds, Dominic N.; Mittendorfer, Bettina
Abstract: Objective: Studies that used an intravenous glucose tolerance test (IVGTT) have suggested that race is an important modulator of insulin sensitivity, β‐cell function, and insulin clearance. However, the validity of the IVGTT has been challenged. Methods: This study assessed insulin sensitivity and insulin kinetics in non‐Hispanic White (NHW, n = 29) and African American (AA, n = 14) people with obesity by using a hyperinsulinemic‐euglycemic pancreatic clamp with glucose tracer infusion, an oral glucose tolerance test (OGTT), and an IVGTT. Results: Hepatic insulin sensitivity was better in AA participants than in NHW participants. Muscle insulin sensitivity, insulin secretion in relation to plasma glucose during the OGTT, and insulin clearance during basal conditions during the hyperinsulinemic‐euglycemic pancreatic clamp and during the OGTT were not different between AA participants and NHW participants. The acute insulin response to the large glucose bolus administered during the IVGTT was double in AA participants compared with NHW participants because of increased insulin secretion and reduced insulin clearance. Conclusions: AA individuals are not more insulin resistant than NHW individuals, and the β‐cell response to glucose ingestion and postprandial insulin clearance are not different between AA individuals and NHW individuals. However, AA individuals have greater insulin secretory capacity and reduced insulin clearance capacity than NHW individuals and might be susceptible to hyperinsulinemia after consuming very large amounts of glucose.